HISTORY EDUCATION TO ENCOURAGE NATIONALISM INTEREST TOWARDS YOUNG PEOPLE AMIDST GLOBALIZATION - Riza Afita Surya; Rif'atul Fikriya (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2021)
History Education to Encourage Nationalism Interest Towards Young People Amidst Globalization. This paper attempts to construct history education concept in establishing nationalism interest towards young people amidst globalization stream. This study is a qualitative research utilizing the case study method due to object studied was derived from reality. Globalization as an inseparable era upon modern societies has been bringing significant impact in many respects of life, one of which is the education field. As part of the historical series, young people at the initial stage of the nationalism movement appeared in Indonesia performed as activators that gained profound responsibility in maintaining and developing such values. Managing historical awareness that is expected to develop national identity has become the basic goal of education. Concepts being discussed here were derived from events analysis and the development of Indonesia education recently. Beside globalization, 21st century challenges also come in the form of Industrial Revolution 4.0 and Z Generation which prompt learning to be more complex. These challenges could be dealt  with continuation innovation, also critical history learning that referring to several theories and prior research is actively capable in increasing nationalism interest amidst globalization.